Tertiary educated Muslim women’s work decision / Peck-Leong Tan, Muhammad Adidinizar Zia Ahmad Kusairee and Norlida Abdul Hamid - Zia Ahmad Kusairee, Muhammad Adidinizar; Abdul Hamid, Norlida (Faculty of Business and Management, 2015)
The participation of women in the labour force has been steadily rising over the years, especially with tremendous human capital investment in educating more women at tertiary levels. However, the tertiary educated women labour participation remains low, particularly among Muslim women. Therefore, this paper explores how tertiary educated Muslim women make their decision to work. This study surveyed 139 tertiary educated women and found their decisions to work are affected by their families’ needs and/or responsibilities, and may not be due to their lives’ goals and dreams. The majority of them work for the sake of money and hence will work if offered jobs meet their expectations in term of salary and position. Furthermore, they will leave the workforce if they need to fulfil their responsibilities at home. Therefore, to retain or to encourage more women especially those with high qualifications to be in the labour market, stakeholders must provide family-friendly jobs and suitable work environment such as flexible working arrangements. More importantly, stakeholders must be able to convince the family members of tertiary educated women to release them to the labour market.